2021
DOI: 10.1002/edm2.286
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for diabetic foot complications among patients with type 2 diabetes in Austria–A registry‐based retrospective cohort study

Abstract: Diabetes mellitus (DM) represents one of the major public health concerns worldwide. Global estimates indicate that 463 million people aged 18-99 years are currently affected by DM and this number is projected to increase to over 700 million people by 2045. The rising prevalence of diabetes can be explained by ageing, population growth and lifestyle alterations. 1-3 Diabetic patients face a high

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Our results also showed that, in contrast to men with T2DM, women have a lower risk of developing DPN. In agreement with other studies, such as by Rossboth et al [ 16 ], this may be explained by the fact that the majority of men with T2DM lack adherence to antidiabetic therapy, resist lifestyle changes and the cessation of smoking, and are more vulnerable to minor trauma of the feet. On the contrary, Khan et al [ 17 ] showed that the female gender is more susceptible to DPN progression.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also showed that, in contrast to men with T2DM, women have a lower risk of developing DPN. In agreement with other studies, such as by Rossboth et al [ 16 ], this may be explained by the fact that the majority of men with T2DM lack adherence to antidiabetic therapy, resist lifestyle changes and the cessation of smoking, and are more vulnerable to minor trauma of the feet. On the contrary, Khan et al [ 17 ] showed that the female gender is more susceptible to DPN progression.…”
Section: Discussionsupporting
confidence: 91%
“…Five studies 5,6,20,25,28 analyzed gender (I 2 = 7%, P = 0.37) using a fixed effects model and showed that men were a risk factor for developing of DFU [OR = 1.84, 95% CI (1.48, 2.29), p < 0.00,001], see Figure 3
Figure 3.Forest plot of the effect of gender on the event of DFU.
…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies 5,7,14,15,19,20,22 analyzed age (I 2 = 77%, p = 0.0003) using a random effects model and showed that advanced age was a risk factor for developing of DFU [MD = 6.04, 95% CI (3.92, 8.16), p < 0.00,001], see Figure 2 Gender. Five studies 5,6,20,25,28 analyzed gender (I 2 = 7%, P = 0.37) using a fixed effects model and showed that men were a risk factor for developing of DFU [OR = 1.84, 95% CI (1.48, 2.29), p < 0.00,001], see Figure 3 Body Mass Index (BMI). Six studies [20][21][22][23]26,29 analyzed BMI (I 2 = 88%, p < 0.00,001) using a random effects model and showed that elevated BMI was a risk factor for developing of DFU [MD = 1.58, 95% CI (0.47, 2.69), p = 0.005], see Figure 4 Disease history Duration of diabetes.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations